Geospatial assessment of climate variability and drought patterns: a case study from Pakistan: Geospatial assessment of climate variability and drought patterns: a case study from Pakistan - Hassan, Sher Shah; Goheer, Muhammad Arif; Farah, Humera; Hafeez, Faiza; Sheraz, Khurram; Fahad, Javaria; Tariq, Aqil (Theoretical and applied climatology, 2025)
Drought substantially threatens Pakistan's agriculture, livestock, and environmental health, specifically in the Thal region. Climate change aggravates drought through extreme temperatures and unpredictable rainfall. This study aims to identify drought-prone districts in Bhakkar, Layyah, Khushab, and Muzaffargarh by correlating climatic parameters with drought vulnerability. Monthly precipitation data was sourced from CHRIPS, while district-level temperature data was obtained from the Climatic Research Unit (CRU) from 1981 to 2020. Vegetation data for six specific years (2001–02, 2004, 2006, and 2019–20) was analyzed using the MODIS product MO13Q1, which offers spatial and temporal resolutions of 250 m and 16 days, respectively. The highest drought severity was noted in 2001 and 2002, severely affecting Muzaffargarh, Layyah, Bhakkar, and Khushab. Moderate drought conditions were observed in 2004 and 2006, with slight improvements in Bhakkar and Layyah. Conversely, 2019 and 2020 saw low or no drought, marked by significant improvements in vegetative health due to increased rainfall. In 2001, higher monsoon temperatures were linked to increased rainfall, affecting STVI and NDVI values. In 2002, concentrated rainfall from July to September showed significant correlations with STVI (0.01) and NDVI (0.05), impacting early-year indices. During the moderate drought conditions of 2006, positive correlations emerged between rainfall and temperature, influencing STVI (0.01) and NDVI (0.05), while temperature correlated with DVI (0.05). In 2019–2020, high monsoon rainfall affected indices differently due to seasonal temperature variations. Pearson’s correlation analysis revealed significant relationships between rainfall and temperature with STVI (0.01) and NDVI (0.05), as well as between temperature and DVI (0.05). This study emphasizes the necessity for ongoing drought monitoring and adaptive management strategies in the Thal region to mitigate the impacts of climate variability on agriculture and vegetation health.